Chronological age estimation using mandibular left permanent second molar in Malaysian children - Dewi Ardini, Yunita; Sukmasari, Susi; Joo Ming, Cheong (2013)
Aim: To provide a quick estimation of chronological age in Malaysian children using mandibular left permanent second molar (M2) and to assess the differences in dental development of M2 between the boys and girls. Methods: 717 orthopantomograms (OPGs) of children between 3 and 16 years old who attended the Unit of Paediatric Dentistry and Orthodontics at IIUM were investigated. The development of M2 was assessed using the eighth grade scheme of Demirjian. 30 OPGs from the sample were randomly selected to test the accuracy of M2 development stages in each age group for chronological age estimation. The remaining 687 OPGs were separated into 14 groups of ages. Chronological age was measured from birth to a given date when OPG was captured. Inter-examiner reliability was tested with Kappa statistic. Statistical data including means and standard deviation of the ages on each stage of M2 mineralization was obtained for both sexes. Results: Inter-examiner reliability was excellent in both sexes with kappa value of 0.848. Statistically significant difference between boys and girls was observed in stages F, G and H of M2 development with girls reaching the stages earlier than boys. Strong relationship was observed between the chronological age and M2 developmental stages. New table for chronological age estimation for Malaysian children was developed. Conclusion: Development of M2 can be considered as a valuable age estimating indicator in Malaysian children population.